Patterns of Homelessness and Implications for HIV Health After Release from Jail - Zelenev, Alexei (AIDS Behav, 2013)
This empirical study examines the association between substance abuse, mental illness, health behaviors and different patterns of homelessness among recently released, HIV-infected jail detainees. Using longitudinal data from a 10-site study, we examine correlates of homelessness, transitions to and from stable housing and the effect of housing on HIV treatment outcomes. Based on our analysis, we found evidence that the transitions from homelessness are closely associated with a reduction in the use of alcohol and illicit drugs, a decline in drug addiction severity, and an improvement in mental health. In addition, we found evidence that disparities in the housing status contributed substantially to the observed gap in the HIV treatment outcomes between homeless and non-homeless patients, including in achievement of virological suppression over time.